BANOVIC STRAHINJA BETWEEN THE SONG AND FILM (Heritage, 2021)
This paper brings insight into the content and analysis of the screenplay “Soko” (The Hawk) (1977) which Saša Petrović (1929–1994) created according to the epic folk song “Banović Strahinja”. Critical approaches to adaptations are numerous and varied, and in this paper we rely on newer theories (Robert Stam, Linda Hutcheon, Dudley Andrew, David Krantz, Thomas Leitch, Sarah Cardwell ...) which perceive the adaptation for other media as an autonomous work of equal status as the original work and which reject fidelity to the original as the criteria for appraisal of adaptations. The comparative approach in this paper was used to see the way in which the narrative, thematic and aesthetic elements were created for the needs of the new media. In addition to the analysis of literary segments, we have included the analysis of film, intertextual and contextual elements, which we considered relevant for the interpretation and assessment of the adaptation. Petrovic is a director who, although he made famous his country's cinematography in the world, did not receive the opportunity to record this film. Special attention in this paper is dedicated to the scene within the tent of the Vlah Alija and the scene with the wolves, and both of them conform to the Genet's notion of paraleptic continuation,  which illustrate Petrović's creative manner in the process of adaptation of the literary work.
Keywords: Soko (The Hawk), Aleksandar Saša Petrović, epic folk song, scenario, adaptation